A proposed framework of life cycle cost analysis for petrochemical wastewater treatment plants - Ilyas, Muhammad; Kassa, Freselam Mulubrhan; Mohd Ridzuan, Darun (Springer, 2021)
Stringent regulations has made it mandatory for petrochemical industries to have wastewater treatment plants for the discharge of safe and environment friendly water. Lack of comprehensive and easy to use framework for life cycle cost analysis hinders the economic evaluation of wastewater treatment plants. This paper presents a comprehensive and easy to use framework for life cycle cost analysis of wastewater treatment plants. The framework includes the purpose of analysis, cost categories, LCC methodology, data collection, calculation of LCC and analysis to select the best alternative process. A brief overview of existing frameworks, need analysis and wastewater process flow is also presented. The proposed framework will provide the foundation through which the life cycle cost of different alternatives can be estimated for effective decision making.